Effect of corn grain in a wet soya waste based total mixed ration silage on goat performance - Ramli, Abdullah; Mohammad Mijanur, Rahman; Mohd Shahmi Hakimi, Mazlishah; Wan Embong, Wan Khadijah (2018)
The utilisation of wet soya waste as feed is low due to difficulties of storage and transportation, which needs to reach normal technical standard and comprehensive utilisation. The aim of this study was to investigate the effect of cracked corn grain as a source of moisture absorbent and energy in a wet soya waste based total mixed ration silage on goat performance. Ten growing goats were assigned to two feeding treatment groups for 84 days. Goats in Group 1 received Napier grass (Pennisetum purpuerum) ensiled with 30% soya waste (w/w) and 8% molasses (w/w) (T1) as control, and Group 2 received same grass ensiled with 30% soya waste (w/w) and 15% cracked corn grain (w/w) (T2). All goats received their respective silage ad libitum after 2 months of fermentation. The pH in T1 silage was 4.1, while pH in T2 silage was 4.0. Goats fed T2 diet showed higher intakes of dry matter, organic matter and metabolisable energy than those of goats fed T1 diet, while it was observed vice versa for neutral detergent fibre intake. However, there was no difference in average daily gain and feed conversion ratio between two treatment diets. Results of this study indicate that cracked corn grain, as a source of moisture absorbent and energy, can be used successfully in wet soya waste based total mixed ration silage for growing goats.